MARKETING STRATEGY THROUGH APPLICATION-BASED DIGITAL MARKETING IN INCREASING CUSTOMER SATISFACTION - Yupiter Mendrofa; Susi Arijanti; Johni Eka Putra (Adisam Publisher, 2024)
Technological developments produce increasingly sophisticated facilities, which can be used as media in developing customer satisfaction-oriented business ventures. One form of technology integration is in marketing practices using digital marketing strategies. Digital marketing strategies are very important as a strategy to increase sales. Currently, establishing effective communication with customers has become a necessity so that customers can understand them. Digital marketing is a marketing or promotional activity for a brand or product using digital media or the internet. The aim of digital marketing itself is to attract consumer interest quickly. The use of digital media in this activity can provide many benefits because the advantages of digital technology enable instant two-way communication between producers and customers, where customers can choose, order, respond and even submit complaints directly wherever and whenever. The important point of the advantage of digital technology is the high frequency of communication or interaction that occurs between producers and customers with a fast information distribution process, which indicates the existence of high frequency brand communication.